Development of the efficiency of winter wheat irrigation in the conditions of Bukhara region - Khudaev I; Yusupov H (Zien Journals, 2023)
Summarizing the information presented in the scientific literature, it shows that determining the timing of planting wheat planted in autumn is one of the important factors of obtaining high and quality grain from irrigated lands. Planting periods have a significant effect on the degree of seed germination, characteristics of the formation of the wheat root system, the speed of development periods, accumulation, the level of plant resistance to cold, the activity of plant photosynthesis, resistance to diseases and pests, grain yield and its quality. has an effect.
Keywords: Planting dates; fertilizer rates; irrigation methods; plant growth